Las adaptaciones curriculares para estudiantes con necesidades educativas especiales, asociadas a la discapacidad en la escuela Cristóbal Colón en la ciudad de Salcedo - Baños Urrutia, Patricia Lorena (2016)
The main objective of this research was: To design a proposal to answer the problem: How do influence curriculum adaptations in the learning process of children with special educational needs associated with disability, in the school Cristobal Colón school Salcedo Canton Cotopaxi province during the school year 2015-2016? The methodology used in the research was: non-experimental because it is educational and because the variables are not manipulated. The results that cast the research are: 17.3% of students with special educational needs: auditory, visual or motor; teachers are not trained to handle these cases; there are no reports on support to these students, neither decision making to improve attention, they don’t know how to make curricular adjustments and the result of the attention given .The contribution of this thesis is a guide of strategies of development of curricular adjustments for students with special educational needs associated with disability, in order to achieve an equitable and inclusive education for all children.